Studi Karakteristik Sesar Bawean (Wilayah Laut Utara Jawa) menggunakan Analisis Turunan dengan Data Gaya Berat - Daffa Andhika Pramadhana; Shelya Trya Rinanda; Yosafat Donni Haryanto (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
The Bawean fault is one of the faults that needs to be watched out for because it is located in the north of Madura Island, which has a population of up to millions of people. One of the mitigation measure that can be taken is the mapping of Bawean Fault to determine characteristics of Bawean Fault. In this research, Bawean Fault mapping was conducted using derivative analysis with gravity data from TOPEX website in the form of FAA (Free Air Anomaly) data. That data, then processed to obtain FHD (First Horizontal Derivative) to determine suspected fault line and SVD (Second Vertical Derivative) value to determine fault mechanism. The steps to obtaining the FHD ((First Horizontal Derivative) value and SVD (Second Vertical Derivative) value are determining the average density using Nettleton method separating regional and residual anomalies using the moving average method, processing regional anomalies with derivative analysis until the FHD (First Horizontal Derivative) and SVD (Second Vertical Derivative) maps are obtained. An cross section was then made on the suspected fault line to determine the exact fault line and fault mechanism. The results obtained from the FHD (First Horizontal Derivative) and SVD (Second Vertical Derivative) map incisions show that the Bawean Fault has a mechanism of thrust fault. However, by considering various sources, it can be concluded that the Bawean Fault has an oblique fault mechanism with the influence of a thrust mechanism.